2000
DOI: 10.1002/etc.5620190433
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory to field validation in an integrative assessment of an acid mine drainage–impacted watershed

Abstract: Abstract-An integrative assessment was conducted in the Puckett's Creek watershed of southwestern Virginia, USA, to investigate the environmental impacts of acid mine drainage (AMD) inputs. Twenty-one sampling stations were categorized into groups based on five degrees of AMD input: (1) none, (2) intermittent acidic/circum-neutral AMD, (3) continuous acidic AMD, (4) continuous circum-neutral AMD, and (5) receiving system stations with at least two levels of dilution. Bioassessment techniques included water/sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 24 publications
6
40
1
1
Order By: Relevance
“…While in situ bioassays can be used to obtain rapid predictive results at low cost, studies dealing with environmental damage have clearly demonstrated that the greatest degree of accuracy is obtained by use of multi-tiered or multidisciplinary studies that incorporate a combination of laboratory and field bioassays with field bioassessments (e.g., Cherry et al 2001;Crane et al 1995;Poirier and Surgeoner 1988;Pontasch et al 1989;Soucek et al 2000). Extensive studies clearly would be needed (and justified) for validating and further developing of our predictive approach.…”
Section: Discussionmentioning
confidence: 99%
“…While in situ bioassays can be used to obtain rapid predictive results at low cost, studies dealing with environmental damage have clearly demonstrated that the greatest degree of accuracy is obtained by use of multi-tiered or multidisciplinary studies that incorporate a combination of laboratory and field bioassays with field bioassessments (e.g., Cherry et al 2001;Crane et al 1995;Poirier and Surgeoner 1988;Pontasch et al 1989;Soucek et al 2000). Extensive studies clearly would be needed (and justified) for validating and further developing of our predictive approach.…”
Section: Discussionmentioning
confidence: 99%
“…As has been shown by Gray and Delaney [23], the effects of low pH and high metal loads on aquatic invertebrate diversity may be similar, and they usually cannot be separated (but, see Soucek et al, Gerhardt et al [58,59]). Similar to the effect of acidity, streams contaminated by metals show reduced richness of many invertebrate groups (Appendix Table A1).…”
Section: Diversitymentioning
confidence: 99%
“…A reduction in the invertebrate taxonomic richness at sites impacted by minewaters has been found by Amisah and Cowx (2000), Malmqvist and Hoffsten (1999), Mori el al. (1999) andSoucek et. al.…”
Section: Introductionmentioning
confidence: 97%
“…Nelson and Roline (1996) also found that the number of taxa in the Ephemeroptera order increased following minewater treatment along with Plecoptera and Trichoptera. Ephemeroptera were identified as being intolerant to elevated metal concentrations by Malmqvist and Hoffsten (1999) and Soucek et al (2000). Leuctra spp.…”
mentioning
confidence: 99%